3 Kompetensi Pegawai Di Kantor Wilayah Badan Pertanahan Nasional Provinsi Bengkulu - Sapruzi, Gaul; Imanda, Antonio; Yusuarsono, Yusuarsono; Kader, Bando Amin C. (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
This research aims to determine the competence of employees at the Regional Office of the National Land Agency of Bengkulu Province. This research is qualitative research presented descriptively. There were 6 informants in this research consisting of3 key informants and 3 main informants. Data collection methods through observation, interviews and documentation. Based on the results of the research and discussion using the theory of Spencer and Spencer (1993:90) there are five indicators used. And it can be concluded that the Competency of Employees at the Regional Office of the National Land Agency of Bengkulu Province has been sufficiently implemented. This can be seen from several indicators, namely: 1.Motive. The motivation carried out by the office in terms of employee performance is by promotion, education and training and technical guidance, motivating employees, giving awards and being involved in activities that foster and improve competency for employees. 2. Character. The employees have abilities or skills that can be used for the advancement of the agency and have the characteristics of employees who are competent in completing a job. 3. Self-concept. That a good employee must have an honest attitude, be disciplined, be responsible at work, be able to complete every task given and be friendly and caring towards other employees. 4. Knowledge. Based on the educational level of the employees, the level of education that employees must have been in accordance with the fields needed by the office starting from high school, diploma, bachelor and master's degree. 5. Skills. Employees’ skills at the office can be implemented through trainings, namely training in leadership, administration, agrarian reform, training for attorneys, land acquisition, skills training and negotiating techniques in dispute resolution, and land conflicts.